Carol Steinbeck - unknown:::Creator::::::::::::
Carol Steinbeck, Charlie Chaplin, and Paulette Goddard in the garden of the Brush Road house. Carol and Goddard are holding dead rattlesnakes. This photo is from Carol Steinbeck's scrapbook.